The late Americans [large type] - Taylor, Brandon (Brandon L. G.) (Random House Large Print, 2023)
During a volatile year of self-discovery in the shared and private spaces of Iowa City, three friends preparing for an uncertain future head to a cabin to bid goodbye to their former lives--a moment of reckoning that leaves each of them irrevocably altered.